Linguistic Complexity and Second Language Advertising Audiences: Is There a Case for Linguistic Exclusion? - Yeboah-Banin, Abena A.; Fosu, Modestus; Tsegah, Marian (Journal of Communication Inquiry, 2017)
In many Anglophone developing countries, the language of most public service advertising is English, a language that is second rather than primary for audiences. Set in a dual-language context where English exists alongside several local languages, as means of interaction, this means that audiences must engage with messages in a language not necessarily preferred for conversation. In addition, messages are often carried on radio, a transient medium where meaning can be lost in the temporality of messages. This increases the task on audiences for processing messages, as the ability to understand most advertisements becomes contingent on their attainment of formal education. While this highlights the critical role of the English language in determining the effectiveness of public service advertisements among second language audiences, it remains understudied in media/communication scholarship. Using a textual analysis of two public service advertising campaigns in Ghana, the study unpacks the English used and examines the implications for audience comprehension.
Research Article
Keywords: Linguistic Complexity, Second Language, Advertising Audience, Linguistic Exclusion